Penerapan Metode Quality Engineering dalam Peningkatan Kualitas Produk UMKM melalui Pengabdian Masyarakat - Siti Nur Hamidah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
This study examines the application of Quality Engineering methods to Micro, Small, and Medium Enterprises (MSMEs) through a community service program. Using a qualitative approach based on literature studies conducted via a webinar at Universitas Sehati Indonesia (USINDO), the research explores how systematic quality improvement strategies can be introduced and adapted for MSMEs to enhance product quality and competitiveness, this study analyzed scientific publications, community service reports, and quality improvement program documentation from 2019-2024. The findings demonstrate that Quality Engineering principles-including Quality Function Deployment (QFD), Seven Basic Tools of Quality, and Statistical Process Control (SPC)-significantly enhance product quality when adapted to SMEs' specific contexts. Case studies reveal improvements ranging from 29.5% to 97.92% across various aspects including customer satisfaction, food safety, and production efficiency. The research identifies key challenges in implementation, including technical knowledge limitations, resource constraints, and difficulties in maintaining long-term changes. The successful integration of Quality Engineering methods depends on active participation from SME stakeholders, approaches tailored to local contexts, and continuous post-program mentoring. This study contributes to developing an integrative framework that combines Quality Engineering principles with practical SME needs, supporting sustainable quality culture development in the SME sector.